Refugee Children and English Language: Challenges From English Language Teachers’ Perspectives - Alrawashdeh, Haneen Abdaljaleel; Kunt, Naciye (Frontiers in Psychology, 2022)
This study aimed at investigating the challenges refugee children face in learning English language from teachers’ perspectives and the challenges of refugees’ English language teachers in Jordan. To achieve this aim, a quantitative approach was implemented using a questionnaire. The findings from this study suggest that refugee teachers acknowledge that they face challenges teaching refugees in terms of cultural competency, preparation, self-efficacy, and the practices they implement, and refugee children face linguistic and psychological challenges in learning English. This study attempted to find out the relationship between teachers’ preparation and their cultural competency, self-efficacy and practices they implement. Then the relationship between refugees' psychological needs and linguistic challenges respectively and teachers’ self-efficacy, cultural competency and practices. Results revealed several significant relationships between challenges and presented them in a model.